Reforming the Fair Use Doctrine in Indonesian Intellectual Property Law: Addressing AI and Digital Creativity through Islamic Legal Perspectives - Ziana Mahfuzzah; Putri Rumondang Siagaian; Cheryl Patriana Yuswar; Muhammad Citra Ramadhan; Dametken Medikhanovna Turekulova (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The rapid advancement of artificial intelligence (AI) and digital creativity has introduced new challenges to Indonesia’s Intellectual Property Rights (IPR) legal framework. The fair use doctrine has not been explicitly regulated under Indonesia’s Copyright Law, resulting in legal uncertainty when copyrighted works are utilized as AI training data or incorporated into digital content. From the perspective of Islamic law, maqāṣid al-sharīʿah offers an ethical and normative framework that balances copyright protection (ḥifẓ al-māl) with the promotion of innovation and intellectual development (ḥifẓ al-ʿaql), thereby fostering justice, public welfare (maṣlaḥah), and an adaptive IPR system. This study aims to analyze the relevance and limitations of the fair use doctrine in the context of AI and digital creativity and to formulate an appropriate direction for legal reform in Indonesia. Unlike previous studies that have tended to examine fair use, software development, or AI-related copyright issues separately, this research integrates intellectual property law, AI governance, and Islamic legal principles within a comprehensive analytical framework. This integrative approach constitutes the novelty of the study by positioning maqāṣid al-sharīʿah as a normative foundation for reforming the fair use doctrine in the era of artificial intelligence and digital creativity. The study employs a normative legal research method using conceptual and statutory approaches through the analysis of primary, secondary, and tertiary legal materials. The findings demonstrate the necessity of reforming the fair use doctrine through explicit legal regulation, clear assessment criteria, equitable compensation mechanisms, and broader coverage of AI-related activities. The study further proposes a maqāṣid al-sharīʿah-based fair use reform model that balances the economic rights of copyright holders (ḥifẓ al-māl) with the advancement of innovation and knowledge (ḥifẓ al-ʿaql), while distinguishing between commercial and non-commercial AI utilization. Such reform is consistent with the objectives of maqāṣid al-sharīʿah in safeguarding intellectual property rights while simultaneously encouraging innovation, thereby contributing to the development of an adaptive and equitable IPR system in Indonesia